Unveiling the "secret" of play in dogs (Canis lupus familiaris): Asymmetry and signals - Cordoni G.; Nicotra V.; Palagi E. (Journal of Comparative Psychology, 2016)
Due to their playful propensity, dogs are a good model to test some hypotheses about play dynamics (length, asymmetry, features of players) and communication (play bow [PBOW]; relaxed open-mouth [ROM] display). We video-recorded 203 play sessions between dogs in an off-leash dog park in Palermo, Italy. Contrary to the expectation, play asymmetry (particularly high in this species) did not differ between stranger and familiar dogs, thus suggesting the limited role of play in forming dominance relationships. Asymmetry negatively affected the duration of the session, whereas the increasing number of players was positively linked to the duration of playful interactions. The number of PBOWs exchanged by players may exert a certain influence on the session length as well. PBOWs were performed independently from the kind of play (locomotor vs. contact) the dogs were engaging in. Conversely, ROMs were preferentially emitted during contact play when "face-to-face" interactions were more likely. Body closeness is also required in case opening the mouth has not a signal function but only preludes a bite. However, in the 82% of cases play bites did not follow a ROM, thus suggesting that dogs place ROMs in the appropriate context to optimize signal detectability. In conclusion, 2 tactics may concur in coping with the asymmetry and unpredictability of play sessions in dogs. First, whenever the asymmetry increases dogs shorten the duration of their sessions thus limiting the risk of possible escalation. Second, dogs make use of a good communicative system based on the reciprocal exchange of playful signals.